CDX2 immunostaining in primary and metastatic germ cell tumours of the testis. (December 2016) - Oz Atalay, Fatma; Aytac Vuruskan, Berna; Vuruskan, Hakan
Objective: To evaluate the immunohistochemical staining pattern of caudal type homeobox 2 (CDX2) protein in germ cell tumours (GCTs) of the testis. Methods: This study reassessed archival tissue samples collected from patients diagnosed with primary and metastatic testicular GCTs for CDX2 immunoreactivity using standard immunohistochemical techniques. Positive nuclear immunostaining was evaluated with regard to both the staining intensity and the extent of the staining. Results: Tissue sections from primary and metastatic testicular GCTs ( n = 104), germ cell neoplasia in situ (GCNis) ( n = 5) and benign testicles ( n = 15) were analysed. The GCNis and benign testicular tissues showed no immunoreactivity for CDX2. Strong and diffuse staining of CDX2 was demonstrated only in the mature colonic epithelium of teratomas in both primary and metastatic GCTs. CDX2 positivity in other tumours (one pure yolk sac tumour, one yolk sac component of a mixed GCT and one pure seminoma) was infrequent, and was only weak and focal. Conclusions: CDX2 immunostaining should be interpreted based on both the staining intensity and the extent of staining so as not to cause misdiagnosis. Teratomas with colonic-type epithelium should be considered in the differential diagnosis if a metastatic tumour with an unknown primary shows prominent CDX2 immunostaining.